Analysis of stock trading volume, leverage, earning volatility, firm size, and dividend yield as determinants of stock price volatility - Aditama, Aditama; Suriawinata, Iman Sofian (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2024)
Recovery Version (See for detail) This study aims to analyze the effect of stock trading volume, leverage, earnings volatility, firm size, and dividend yield on stock price volatility in companies listed in the consumer goods industry sector on the Indonesia Stock Exchange (IDX). The period in this study is 5 years from 2018 to 2022. Samples were taken using a purposive sampling method with the criteria that they were registered in the consumer goods industry sector from 2016, continuously published annual financial reports, and did not perform stock splits during the study period. Thirty-five companies met these criteria. The data in this study are secondary, obtained from the company's financial statements. Multiple linear regression is used as a data analysis method. The results of this study indicate that stock trading volume, earnings volatility, and firm size have a significant positive effect on stock price volatility. The higher the value of stock trading volume, earnings volatility, and firm size, the higher the stock price volatility. Conversely, leverage has a negative and significant effect on stock price volatility. The higher the leverage, the lower the stock price volatility. Meanwhile, dividend yield has no impact on stock price volatility.